A remarkable new species of Kiotina Klapálek, 1907 (Plecoptera: Perlidae) from China - Mo, Raorao; Wang, Guoquan; Li, Weihai; Murányi, Dávid (Zootaxa, 2019)
A remarkable new species of the genus Kiotina Klapálek, 1907 is described, K. bilobata sp. nov. both from Guangdong and Zhejiang provinces of China. The taxonomic relationships with related species are discussed in this paper.